Super‐mini percutaneous nephrolithotomy (PCNL) vs standard PCNL for the management of renal calculi of <2 cm: a randomised controlled study. (31st July 2020) - Guddeti, Raja Sekhar; Hegde, Padmaraj; Chawla, Arun; de la Rosette, Jean J.M.C.H.; Laguna Pes, Maria Pilar; Kapadia, Aseem
Abstract : Objective: To compare the effectiveness and safety of standard percutaneous nephrolithotomy (sPCNL) and super‐mini PCNL (SMP). Patients and Methods: A total of 150 patients presenting with renal calculi of <2 cm were randomised to either sPCNL (Group 1) or SMP (Group 2). Randomisation was based on centralised computer‐generated numbers. Variables studied included: stone‐free rates (SFRs), operative time, intra‐ and postoperative complications, postoperative pain score, analgesic requirement, and hospital stay. Statistical analysis was performed using a t ‐test or Mann–Whitney U ‐test for continuous variables and chi‐squared test or Fisher's exact test for categorical variables. Results: Between September 2018 and April 2019, 75 patients were included in each group. The SFRs of the groups were similar (97.33 vs 98.66%, P = 0.56). The mean (sd) operative time was significantly longer in Group 2, at 36.40 (14.07) vs 23.12 (11.96) min ( P < 0.001). The mean (sd) decrease in haemoglobin was significantly less in Group 2, at 3.0 (4.9) vs 7.5 (6.5) g/L ( P < 0.001). The mean (sd) pain score at 24 h was significantly lower in Group 2, at 0.3 (0.46) vs 0.75 (0.53) ( P < 0.001). The mean (sd) analgesic requirement was significantly less in Group 2, at 67 (22.49) vs 91.5 (30.56) mg tramadol ( P < 0.001). The mean (sd ) hospital stay was significantly less in Group 2, at 28.38 (3.6) vs 39.84 (3.7) h ( P < 0.001). Conclusions: SMP is equally as effective as sPCNL for managing renal calculi of <2 cm, with improved safety. Although SMP is associated with a longer operative time, it has a significantly lower incidence of bleeding and postoperative pain, and a shorter hospital stay.